Kesan Modenisasi terhadap perayaan Gawai Dayak di daerah Bau, Sarawak - Windy, Inki (Universiti Malaysia Sarawak (UNIMAS), 2007)
This research aims to examine how far the effect of modernization influences the celebration of Gawai Dayak at Bau district. Besides that, this research is also being conducted to find out the perception of the Bau community with regards to modernization Gawai Dayak.